Intangible Knowledge Capital and Innovation in China - Belton M. Fleisher; William H. McGuire; Adam Nicholas Smith; Mi Zhou (Institute for the Study of Labor (IZA), 2013)
Intangible knowledge capital (IKC) technology produced by workers but not embodied in them can offset the middle income trap as China exhausts the benefits of international technology transfer. IKC is productivity-enhancing among Chinese enterprises more so in domestically owned than in foreign invested enterprises. Consistent with other research, we find that China's IKC generates patents in China, but fewer than in major industrialized economies. Among domestically owned enterprises, IKC growth has flowed more toward higher-tech, export-oriented industries, while among foreign invested enterprises, it has been oriented more toward domestic sales.
Keywords: O31; O33; O34; O43; P33; 330; intellectual capital; technology; economic growth; intellectual property; Asia; China